2009
DOI: 10.1002/col.20503
|View full text |Cite
|
Sign up to set email alerts
|

Size effect of color patches for their color appearance with foggy goggles simulating cloudy crystalline lens of elderly people

Abstract: The cataract eyes can be characterized by three elements; luminance, spectral distribution, and scatter, which are perceived as brightness, color, and fogginess, respectively. Change of any of the three elements may affect visual performance. The foggy element, which refers to the perception associated with a change in the optical scatter of the crystalline lens, causes deterioration of the visual acuity, pattern perception, and an uncomfortable foggy appearance over the visual field. Moreover, it also affects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…It is found that the results of most of the color studies have been done in laboratory or testing room, or using color samples and simulated images in articles, or computer programs with color samples or other color elements . Nevertheless, few studies have combined the method assessment with an actual setting context in order to evaluate the effects of participants in this context .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is found that the results of most of the color studies have been done in laboratory or testing room, or using color samples and simulated images in articles, or computer programs with color samples or other color elements . Nevertheless, few studies have combined the method assessment with an actual setting context in order to evaluate the effects of participants in this context .…”
Section: Resultsmentioning
confidence: 99%
“…The fact of working with older people implies greater difficulty in moving to a laboratory or research center, due to their vulnerability; what entails having to perform the experiments in their habitual space, with environmental variables that are difficult to control. It is important to highlight the light factor, that is, to study the effects of color under different illumination conditions . In these cases, illumination is introduced as a changeable factor for their experiments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations